Metaphor as an Element of Persuasion in Political Discourse - Marek Hampl (Communications - Scientific letters of the University of Zilina, 2012)
This paper deals with the concept of metaphor as manifested in political discourse. The focus of the paper is on how metaphors achieve their persuasive function in political discourse and how politicians make use of metaphors. The paper also provides general theoretical background for the theories of metaphor.Furthermore, attention is paid to the concepts of persuasion and manipulation in political discourse. The actual examples of metaphorical language are represented by metaphors from the Cold War period.